Access to climate change technology by developing country : a practical strategy - Cannady, Cynthia (2009)
Suggests that a fundamentally different approach should be taken in enhancing developing country access to climate change technologies. Indicates that it should strategically focus on the capacity of developing countries themselves innovating and contributing to climate technology development on fair and equal terms with developed country partners.